Optimal design of multipurpose batch plants 1. Problem formulation - Barbosa,Póvoa AP; Macchietto,S (Computers and Chemical Engineering, 1993)
A formulation is presented for the optimal selection of both equipment units and the network of connections for multipurpose batch plants so as to satisfy given production requirements for a variety of products. The model includes very general constraints and objective functions and permits to simultaneously optimise the structural aspects of the plant and the associated production schedule, accounting for both capital cost of equipment units and pipework, operating costs, and revenues. A special novelty of the formulation is that it provides the possibility of generating directly the optimal connectivity between process units, sizing and costing of all transfer lines, and the optimal storage policies (and associated vessel sizes, if any) for stable intermediates without the need for a priori assumptions (e.g. unlimited storage, etc). © 1992, Pergamon Press Ltd. All rights reserved.